A study of the bijon industry in Bulacan and its vicinity - Cruz, Feliciana R.; Perez, Presentacion T. (1959)
(No Abstract)
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Food industry and trade -- Philippines -- Bulacan